Clinico-pathological correlation in case of BRAT1 mutation - Szymańska, Krystyna; Laure-Kamionowska, Milena; Szczałuba, Krzysztof; Koppolu, Agnieszka; Furmanek, Mariusz; Kuśmierska, Katarzyna; Boniel, Snir; Płoski, Rafał; Rydzanicz, Małgorzata (Folia Neuropathologica, 2018)
The clinical picture of BRCA1-associated protein required for ATM activation-1 (BRAT1) comprises retractable early-onset epileptic encephalopathy, progressive microcephaly, and early demise. Both, inter- and intrafamilial variations of features of BRAT1-associated disease have been described. Here, the familial case of a brother and sister with homozygous pathogenic variants in BRAT1 is presented with special emphasis on differences in seizure type/onset and central nervous system lesions. The neuropathology is extensively discussed and hypotheses put forward that may shed light on etiology of brain symptomatology within the context of BRAT1 mutations.